GENERAL THEORETICAL ASPECTS OF FORMING MILITARY POLICE FOR PROVIDING LEGITIMACY IN THE ARMED FORCES OF UKRAINE - Кузьмич, Ігор Іванович; Кузьмич, Іван Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of the article is to point out particularities, drawbacks, as well as give propositions as to efficient reforming Military service of Justice into Military police grounding on the analysis of laws in force, legal literature and international experience. Methods of research: the methodological base of research is the following general and special methods of perception – dialectical method of scientific learning of reality, analysis, synthesis, systematic structural method, as well as comparative legal and formal logical methods. Results: as a result of scientific search the international practice of forming military police has been studied, as well as the possibilities of its using in Ukraine, also the directions of improvement of normative and legal provision of military police’s activity have been determined. Discussion: national and state security is provided by the system of state bodies which activity is meant to protect social and state system (constitutional order), state independence (state sovereignty), territorial integrity (untouchability of the borders), military (defensive), economical, scientific and technical potential. Supporting national security is one of the main functions of a society and state. Constituent elements of national security is also a social security, legal order and more narrow branches of social relations in the area of national security, such as: safety of labour, safety of traffic, aviation safety, informational safety, safety of food, regional safety etc. as well as main directions of state policy in the sphere of state security defined by the Law of Ukraine «About National Security of Ukraine». Ukraine’s Constitution, article 17, proclaims that providing state security and defense of a state border relies on the corresponding legal bodies, also on the military force which organization and order of activity are specified by law.